TRADITIONAL RETAIL BUSINESS DEVELOPMENT MODEL IN THE NORTHEAST REGION ALONG THE BORDER OF THAILAND - Arnupap Kerepat; Thanasuwit Thabhiranrak, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The objectives of this research were to: firstly, study the level of satisfaction in purchasing products, product quality, service quality, and money value of consumers in the traditional retail businesses in the northeast region along the border of Thailand, secondly, study the influence of variables affecting the success of traditional retail businesses in the northeast region along the border of Thailand, and thirdly, develop the traditional retail business model in the northeast region along the border of Thailand. The samples consisted of 380 people living in 7 provinces along the border of Thailand, which were Loei province, Nong Khai province, Bueng Kan province, Mukdahan province, and Amnat Charoen province; collected 54 people each, and Nakhon Phanom province and Ubon Ratchathani province; collected 55 people each. The research results indicated that the consumers’ opinions towards satisfaction in purchasing products, product quality, service quality, and the value for money of consumer's perspectives were rated at a high level. In addition, factors including purchasing satisfaction, product quality, quality of service, and value for money affected the success of traditional retail businesses. Lastly, the traditional retail business model in the northeast region along the border of Thailand should focus on product quality, value for money, purchasing satisfaction, and service quality.